Thermal pyrolysis conversion of methane to hydrogen (H2): A review on process parameters, reaction kinetics and techno-economic analysis - Chan, Yi Herng; Chan, Zhe Phak; Serene Lock, Sow Mun; Yiin, Chung Loong; Foong, Shin Ying; Wong, Mee Kee; Muhammad Anwar, Ishak; Quek, Ven Chian; Shengbo, Ge; Lam, Su Shiung (Elsevier B.V., 2023)
Hydrogen (H2) is a promising renewable energy which finds wide applications as the world gears toward low-carbon economy. However, current H2 production via steam methane reforming of natural gas or gasification of coal are laden with high CO2 footprints. Recently, methane (CH4) pyrolysis has emerged as a potential technology to generate low-carbon H2 and solid carbon. In this review, the current state-of-art and recent progress of H2 production from CH4 pyrolysis are reviewed in detail. Aspects such as fundamental mechanism and chemistry involved, effect of process parameters on the conversion efficiency and reaction kinetics for various reaction media and catalysts are elucidated and critically discussed. Temperature, among other factors, plays the most critical influence on the methane pyrolysis reaction. Molten metal/salt could lower the operating temperature of methane pyrolysis to < 1000°C, whereas plasma technology usually operates in the regime of > 1000°C. Based on the reaction kinetics, metal-based catalysts were more efficient in lowering the activation energy of the reaction to 29.5-88 kJ/mol from that of uncatalyzed reaction (147-420.7 kJ/mol). Besides, the current techno-economic performance of the process reveals that the levelized cost of H2 is directly influenced by the sales price of carbon (by-product) generated, which could offset the overall cost. Lastly, the main challenges of reactor design for efficient product separation and retrieval, as well as catalyst deactivation/poisoning need to be debottlenecked.